Metabolic reprogramming of osteoclasts represents a therapeutic target during the treatment of osteoporosis - Taubmann, Jule; Krishnacoumar, Brenda; Böhm, Christina; Faas, Maria; Müller, Dorothea; Adam, Susanne; Stoll, Cornelia; Böttcher, Martin; Mougiakakos, Dimitrios; Sonnewald, Uwe; Hofmann, Jörg; Schett, Georg; et al. (Scientific Reports, 2020)
Osteoclasts are specialised bone resorbing cells that control both physiological and pathological bone turnover. Functional changes in the differentiation and activity of osteoclasts are accompanied by active metabolic reprogramming. However, the biological significance and the in vivo relevance of these events has remained unclear. Here we show that bone resorption of differentiated osteoclasts heavily relies on increased aerobic glycolysis and glycolysis-derived lactate production. While pharmacological inhibition of glycolysis did not affect osteoclast differentiation or viability, it efficiently blocked bone resorption in vitro and in vivo and consequently ameliorated ovariectomy-induced bone loss. Our experiments thus highlight the therapeutic potential of interfering with osteoclast-intrinsic metabolic pathways as possible strategy for the treatment of diseases characterized by accelerated bone loss.
CRIS-Team Scopus Importer:2020-12-11